Thomas Grippa: capstone - Grippa, Thomas, artist (Colorado State University. Libraries, 2015)
The artist's statement: The majority of my past work has revolved around internal struggles and the things I'm most afraid of. As of more recently my work has been a blatant representation of the lack of ability I have in regards to dealing with said internal struggles and the mounting stress of everyday life. In an attempt to embrace these struggles I've decided to paint myself showing exactly how I feel with the mounting pressure of having to create and perform at any given minute; i.e. peeling my own skin off, and puking out my own skeleton. These paintings are done on mounted Masonite, and I was trying to take a more moralistic approach in mark making and color pallet. I made these pieces because I thought it would be fun trying to create impossible situations (like a skeleton ripping off bones to uncover skin) and to also deal with my stress and internal struggles of my final semester as a painting student at Colorado State. My second body of work stems from past ideas I've had while trying to represent cancer. The pieces I've made in regards to cancer have been very experimental and are bordering somewhat on the edge of sculpture. They are made with melted plastic, drywall compound, spray foam, and oil paint on a mounted Masonite panel. When I started this body of work several semesters ago my Uncle had just been diagnosed with stage-four throat cancer. The piece I made back then was an attempt to deal with all of the possibilities and changes that could potentially come from such a diagnosis. On the bright side my Uncle is now clear of any cancer, I however have continued making and evolving my work in regards to this event. My third body of work is based around a piece I did using the voronoi algorithm to map out natural disasters around the United States. I have evolved this idea into mapping out cancer cells, and skulls to better fit my theme for this semester. I make these images in Rhino using the voronoi algorithm, and then I use the laser cutter to cut the negative space out of three-millimeter birch plywood.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting